Anti-allodynic effect of intrathecal processed Aconitum jaluense is associated with the inhibition of microglial activation and P2X7 receptor expression in spinal cord. Issue 1 (December 2016) - Yang, Jihoon; Park, Keun; Yoon, Jae; Bae, Hong-Beom; Yoon, Myung; Choi, Jeong
Abstract Background For their analgesic and anti-arthritic effects, Aconitum species have been used in folk medicine in some East Asian countries. Although their analgesic effect is attributed to its action on voltage-dependent sodium channels, they also suppress purinergic receptor expression in dorsal root ganglion neurons in rats with neuropathic pain. In vitro study also demonstrated that the Aconitum suppresses ATP-induced P2X7 receptor (P2X7R)-mediated inflammatory responses in microglial cell lines. Herein, we examined the effect of intrathecal administration of thermally processed Aconitum jaluense (PA) on pain behavior, P2X7R expression and microglial activation in a rat spinal nerve ligation (SNL) model. Methods Mechanical allodynia induced by L5 SNL in Sprague-Dawley rats was measured using the von Frey test to evaluate the effect of intrathecal injection of PA. Changes in the expression of P2X7R in the spinal cord were examined using RT-PCR and Western blot analysis. In addition, the effect of intrathecal PA on microglial activation was evaluated by immunofluorescence. Results Intrathecal PA attenuated mechanical allodynia in a dose-dependent manner showing both acute and chronic effects with 65 % of the maximal possible effect. The expression and production of spinal P2X7R was increased five days after SNL, but daily intrathecal PA injection significantly inhibited the increase to the level of naïve animals. Immunofluorescence of the spinal cord revealed a significant increase in P2X7R expression and activation of microglia in the dorsal horn, which was inhibited by intrathecal PA treatment. P2X7R co-localized with microglia marker, but not neurons. Conclusions Intrathecal PA exerts anti-allodynic effects in neuropathic pain, possibly by suppressing P2X7R production and expression as well as reducing microglial activation in the spinal cord.